Respons(A)bility: Weaving Words of Responsibility Through Story - Belanger, Mariel (Percées, 2023)
This AuNTIe paper calls for better ways of being and doing in academe than the status quo practices across universities. Mad Native Auntie sits you down for a class in understanding why Indigenous ways of knowing are not tools like interview or survey for academics to colonize as free-for-all methodological use. Auntie addresses the demoralization that occurs when the Indigenous “other” is made teacher of pan-Indigenous epistemology. I discuss my understanding of duty-of-care through research, taking precautions to predict what could be happening for others when applied to the understanding of performance ethnography as course work.